2016
DOI: 10.14687/jhs.v13i3.3848
|View full text |Cite
|
Sign up to set email alerts
|

Examining teachers’ opinions regarding the organizational forgiveness in reference to several variables<p>Öğretmenlerin örgütsel affediciliğe ilişkin görüşlerinin çeşitli değişkenlere göre incelenmesi

Abstract: The aim of this study is to reveal the teacher views on forgiveness behavior in their interpersonal relationships with other teachers at school and analyze their views in reference to several variables (gender, subject field, seniority, school type, length of service at school and number of students at school). In the study, "Convergent parallel design", a mixed research method was used. The participants in the quantitative part of the study were comprised of 252 teachers working at public schools in Ankara ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…Other studies have concluded that trainers and physical education and sports teachers were more likely to seek revenge than they were to forgive (Güllü & Şahin, 2017) and that this was the case for teachers, too (Nayir & Kepenekçi, 2016). However, in this study, nurses' intention to get revenge was low.…”
Section: Discussioncontrasting
confidence: 73%
“…Other studies have concluded that trainers and physical education and sports teachers were more likely to seek revenge than they were to forgive (Güllü & Şahin, 2017) and that this was the case for teachers, too (Nayir & Kepenekçi, 2016). However, in this study, nurses' intention to get revenge was low.…”
Section: Discussioncontrasting
confidence: 73%